THE RELATIONSHIP BETWEEN MOTHER’S OCCUPATION, ADEQUACY LEVELS OF ENERGY AND PROTEIN WITH INFANT’S NUTRITIONAL STATUS - Dian Anita Nilawati; Lailatul Muniroh (The Indonesian Journal of Public Health, 2020)
Infant is one of vulnerable groups that have nutritional problems. High prevalence of nutritional problems could affect nutritional status that become an important concern. The determining factor of nutritional status includes nutritional intake and maternal occupation. The purpose of this study was to determine the relationship between maternal occupation and nutritional intake, with nutritional status of infants aged 6-12 months. This study used cross-sectional design, with nutrional status of infants as dependent variable; intake of the food energy sufficiency level and protein sufficiency level. Subject was selected by simple random sampling technique. The interview was conducted on 88 mothers of infants aged 6-12 months, which used questionnaire, form food recall 2x24 hours (breastfeeding and complementary feeeding), and anthropometric measurements (W/L index). Data analyzed used Spearman-Rank test and Coefficient Contingency. The results of this study showed that most of the infants had normal nutritional status (76,1%). Maternal occupation (p=0,025) had correlation with nutritional status. The food energy sufficiency level (p=0,047) had correlation with nutritional status and protein sufficiency level (p=0,016) had correlation with nutritional status. The conclusion of this study is infant who get the sufficiency level of energy and protein sufficiency level adequate has normal nutritional status. Wasting infant tend to have inadequate energy and protein intake. This study suggest mothers to give complementary feeding appropriately the quantity and according to the stage of giving food to infant. Keywords: maternal occupation, nutritional status of infant, the sufficiency level of energy, protein sufficiency level